Tasty Tales - Brennan, Frank (United Kingdom Cambridge University Press, 2009)
Short stories themed around food and drink: a bed and breakfast owner is determined that a guest should try her famous 'Full English Breakfast'; a scientist invents an additive that increases peoples' attraction to certain food; a young boy learns to cook with the help of a great uncle and a magic ingredient; and a Japanese master chef must prepare his own last meal. This paperback is in British English.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents
Keywords: Short Stories; Fiction; Reading books; Intermediate level; English language